Causal effect of sex hormone-binding globulin and testosterone on coronary heart disease: A multivariable and network Mendelian randomization analysis. (15th September 2021) - Li, Yunxia; Si, Shucheng; Hou, Lei; Yuan, Tonghui; Chen, Xiaolu; Liu, Congcong; Li, Wenchao; Li, Hongkai; Liu, Yanxun; Xue, Fuzhong
Abstract: Background: Although observational studies have shown an association between sex hormone-binding globulin (SHBG), testosterone (T) and cardiovascular diseases (CVD), controversy remains. In this study, we aim to explore the causal effects of SHBG and T on Coronary heart disease (CHD). Methods: We used univariable, network and multivariable mendelian randomization (MR) analysis to investigate the causal effect of SHBG and T on CHD. We performed inverse variance weighted (IVW) MR as the primary analysis, with the robustness of this approach further tested by other methods in sensitivity analysis. The SHBG and T were collected from the UK Biobank data, about 180, 000 men aged 40 to 69 years. CHD was collected from CARDIoGRAMplusC4D 1000 Genomes-based GWAS, which was a meta-analysis including 48 studies and involving 60, 801 CHD cases and 123, 504 controls. Results: Using univariable MR-IVW, the results suggested that a one standard deviation (SD) increase in SHBG, the risk of CHD decreased by approximately 14% (OR (95% CI): 0.86(0.76, 0.97)), and that a SD increase in total testosterone (TT), the risk also decreased, approximately 8% (OR (95% CI): 0.92(0.85, 0.99)). Multivariable MR showed that both SHBG and TT had no direct causal effect with CHD (a SD increase in SHBG: OR (95% CI):0.75(0.57, 1.00), P = 0.053; a SD increase in TT: OR (95% CI): 1.05(0.90, 1.22), P = 0.53). In the network MR analysis, the results suggested that TT might act as mediator in the causal pathway from SHBG to CHD and account for 93% of the total effect of SHBG on CHD, and that SHBG might be a mediator in the causal pathway from TT to CHD and account for 67% of the total effect of TT on CHD. Conclusions: Genetically predicted SHBG and TT were negatively correlated with CHD in both univariable and network MR, which may provide a causal explanation behind the observed conclusion. In addition, TT and SHBG had a bidirectional causal effect. Further work is required to disentangle the downstream effects of SHBG/TT on CHD and the molecular pathways involved, as the simultaneous regulation of SHBG and TT may make it a viable strategy for the prevention or treatment of CHD. Highlights: Multivariable MR showed that both SHBG and TT had no direct causal effect with CHD (a SD increase in SHBG: OR (95%CI):0.75(0.57, 1.00), P = 0.053; a SD increase in TT: OR (95%CI): 1.05(0.90, 1.22), P = 0.53). In the network MR analysis, the results suggested that TT might act as mediator in the causal pathway from SHBG to CHD and account for 93% of the total effect of SHBG on CHD, and that SHBG might be a mediator in the causal pathway from TT to CHD and account for 67% of the total effect of TT on CHD.